MENYELAMATKAN ANAK MASUK PENJARA MELALUI PENDAMPINGAN Studi Kasus Di Provinsi Lampung - Alit Kurniasari (Sosio Konsepsia, 2009)
Prisoning of a child is the last place for child in court, but cases of children in jail despite mild cases still found. Assistance for children in conflict with the law (ABH) is important, especially in legal and psychosocial aspects, starting when the children were arrested, and after the children had faced the legal process because it is never too late to save the children from being sentenced to jail. The evidence suggests that the impact of the imprisonment of children has more negative than the good results. Result of assistance from NGOs in the province of Lampung, in fact can ensnare adult perpetrators who had been "above the law" evenrescuing children from the arbitranJ of law enforcement. The presence of PK (Bapas) as a companion after a child faced lzis/her legal process, in fact is still weak to save the children from prison as well as assistance in prisons is not yet sufficient, so the psychosocial assistance for ABH, primarily to minimize the effect of children imprisonment and prepare the childre1Z's the psychosocial as well as environment life, is urgently needed. In order to give optimum result, increase in the companion's capacity, coordination and cooperation between the companion as a social worker (correctional) is needed. It is necessary to set up a Child Protection Forwn, which consists of government agencies and NGOs related to the protectioll of children in conflict with the law.